Sereniss[i]mus Potentiss[i]musq[ue] Princ. Ac Dom. D. Matthias Coronatvs Rex Hvngariæ Designatvs Bohemiæ, Archidvx Avstriæ, Dvx Bvrgvndiæ, Styriæ, Carinthiæ, Carniolæ, Et Wirtemb. Marchio Moraviæ, Comes Habspvrg, Et Tyrolis - Ullrich, Heinrich (1619)
Matthias, Heiliges Römisches Reich, Kaiser